Examining the evolution of waqf regulations in Selangor: an analysis of the governance framework and transformative approach - Abdul Manaf, Zati Ilham; Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah (IIUM Press, International Islamic University Malaysia, 2019)
The inadequacy of comprehensive laws for Waqf administration is one of the main issues that has limited the development of Waqf in Malaysia. Whilst most states in Malaysia rely on their Administration of Islamic Law enactments, in 1999 Selangor pioneered a Waqf enactment which specifically oversees Waqf administration and management. With the promulgation of the Selangor Waqf Enactment 1999, the administration of Waqf in Selangor became more regulated and structured. However, as matters pertaining to Waqf practices became more complex, Selangor repealed its 1999 Waqf Enactment and replaced it with the 2015 Waqf Enactment. This research therefore analyses the evolution of Waqf in Selangor through the two respective enactments, by identifying the changes in practices and scrutinising the rationales for the development of the laws. It also analyses how the laws have impacted the Waqf governance framework in the state. By assessing the position of the 2015 Waqf Enactment, it determines whether the current legislative demand posed by Waqf development in the state is met and whether the change in approach should be followed by other states in Malaysia. Doctrinal legal research is utilised to examine the two enactments respectively. Legislative Assembly Proceedings related to the promulgation of the respective enactments were also examined to further understand the reasoning behind the repeal and the introduction of certain provisions. It is found that although the 2015 Waqf Enactment is more comprehensive than the 1999 Waqf Enactment, further improvements can be made to better achieve transparency and accountability on the part of the Waqf administrator